Logistics of Guinea Worm Disease Eradication in South Sudan - Jones, Alexander H. (The American Society of Tropical Medicine and Hygiene, 2014)
From 2006 to 2012, the South Sudan Guinea Worm Eradication Program reduced new Guinea worm disease (dracunculiasis) cases by over 90%, despite substantial programmatic challenges. Program logistics have played a key role in program achievements to date. The program uses disease surveillance and program performance data and integrated technical–logistical staffing to maintain flexible and effective logistical support for active community-based surveillance and intervention delivery in thousands of remote communities. Lessons learned from logistical design and management can resonate across similar complex surveillance and public health intervention delivery programs, such as mass drug administration for the control of neglected tropical diseases and other disease eradication programs. Logistical challenges in various public health scenarios and the pivotal contribution of logistics to Guinea worm case reductions in South Sudan underscore the need for additional inquiry into the role of logistics in public health programming in low-income countries.